INCIDENCE AND INTENSITY OF PESTS AND DISEASES ATTACKING RICE PLANTS (Oryza sativa L.) IN WEDOMARTANI VILLAGE - Wibawaningtyas, Kurnia Ramadhani; Maura Falina Dinisa; Dhea Ezra Adelia Marpaung; Fadhil Dzaky Ash Shodiqy (Agrofarm: Jurnal Agroteknologi, 2025)
The increasing food needs of the Indonesian population underline the critical role of rice (Oryza sativa L.) in national food security, but production is often constrained by attacks from pests and diseases. This study aimed to determine the incidence and intensity of key pests (grasshoppers and rice bugs) and diseases (blast and tungro) in a rice field in Wedomartani Village through the application of a systematic W-pattern sampling technique. Observations were conducted four times over a 5-day interval, with samples taken from 50 rice plants. The quantitative approach used formulas to calculate the percentage of Disease Incidence and Disease Severity. The results showed a consistently increasing pattern of infestation for all pests and diseases throughout the observation period. Grasshopper incidence reached 100% by the third observation, with a peak intensity of 34.22% (moderate category) at the fourth observation. Rice bug incidence peaked at 98%, with an intensity of 18.22% (low category). Both blast and tungro incidence reached 100%, with blast severity peaking at 26.22% (moderate category) and tungro severity reaching 50.67% (moderately high category). The high levels of incidence and intensity are primarily supported by environmental conditions conducive to pest and disease development, such as high humidity for blast and the availability of preferred food sources for rice bugs. These findings affirm the urgent need for comprehensive Integrated Pest Management (IPM) strategies, including synchronized planting, field sanitation, and biological control, to secure optimal rice production in the area.